2007
DOI: 10.2319/101206-422.1
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance Open-Bite Treatment with Zygomatic Anchorage

Abstract: Objective: To evaluate the dentoalveolar and skeletal effects of the new-generation open-bite appliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
0
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(154 citation statements)
references
References 17 publications
11
123
0
20
Order By: Relevance
“…In growing patients, relative intrusion of the molars is recommended to control for vertical development of the jaws. 1 In adult patients, absolute intrusion of posterior occlusal segments can be performed with the aid of temporary anchorage devices, [2][3][4][5][6][7][8][9][10] and surgical treatment can be considered as well. The choice of treatment protocol depends on many factors, including esthetic and occlusal aspects, morphologic characteristics, and the severity of the skeletal anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…In growing patients, relative intrusion of the molars is recommended to control for vertical development of the jaws. 1 In adult patients, absolute intrusion of posterior occlusal segments can be performed with the aid of temporary anchorage devices, [2][3][4][5][6][7][8][9][10] and surgical treatment can be considered as well. The choice of treatment protocol depends on many factors, including esthetic and occlusal aspects, morphologic characteristics, and the severity of the skeletal anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…The same note was observed in a previous investigation which revealed that buccal tipping of posterior maxillary segment was inevitable because of the location of the line of force in relation to the center of resistance of the segment. It has been reported that, tipping of buccal segment not only impaired posterior occlusion but also impeded successful elimination of the SAOB because of the interferences created between upper and lower teeth (10) .…”
Section: Results' Interpretationmentioning
confidence: 99%
“…It is often the outcome of a vertical growth pattern and increased maxillary posterior vertical height. Noteworthy, surgical treatment of SAOB malocclusion by conventional Le Fort 1 surgery was considered as the typical treatment or the first option for SAOB malocclusions (10) . Unfortunately, patient acceptance of this treatment modality was almost negative and not accepted by most of the current research patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The most effective treatment option in adult patients with skeletal open bite is surgical repositioning of the maxilla or both jaws. 1,3 The results of surgery to reduce the mandibular plane angle and to close the open bite by closing rotation of the mandible with only mandibular surgery have been shown to be highly unstable because this rotation lengthens the ramus and stretches the muscles of the pterygomandibular sling. 4 Therefore, a surgical procedure involving superior repositioning of the maxilla with a Le Fort I osteotomy is recommended to obtain more stable and predictable results for the surgical correction of skeletal open bite.…”
Section: Introductionmentioning
confidence: 99%